Giant verruca vulgaris: a case report (Faculty of Medicine Universitas Indonesia, 2009)
Common wart is the most frequent clinical lesion caused by human papillomaviruses (HPVs). Giant, chronic, isolated, and solitary lesion is uncommon. We reported a case of giant verruca vulgaris in a 66 year-old man on left dorsal pedis that slowly enlarged and hardened in 10 years. It was a solitary hyperkeratotic verruca vulgaris, grey brownish in color, circumscribe, round, and 3x2.4x0.4 cm in size. Histopathologic examination revealed compact hyperkeratosis/orthokeratosis, many koilocytes in the granular and upper spinous layer, acanthosis, and elongated rete ridges that were pointing radially toward the center of the lesion. Polymerase chain reaction (PCR) and in situ hybridization failed to identify HPV DNA. The patient was successfully treated with salicylic acid 40% ointment. (Med J Indones 2008; 18: 135-8)Key words: papilloma viruses, hyperkeratosis, orthokeratosis